(untitled) (Journal of Enam Medical College, 2014)
Fibrodysplasia Ossificans Progressiva (FOP) is an inherited disease in which progressive ossification of striated muscles, tendons, ligaments and other connective tissues forming bridges of extra bones across the joints leads to severe disability and there are associated characteristic congenital skeletal malformations. FOP is also known as Stoneman’s syndrome. The case we report here is a 23-year-old male with the clinical and radiologic characteristics of FOP. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19682 J Enam Med Col 2014; 4(2): 126-129